AN AEROBIOLOGICAL APPROACH TO GROUNDNUT RUST - C. S. ARSULE,; B.N. PANDE, (The Bioscan, 2011)
An aerobiological survey was conducted over the groundnut (Arachis hypogea L. Var.JL-24) fields at Newasa (Ahmednagar) for two consecutive kharif seasons of 2007 and 2008 by employing volumetric Tilak air sampler kept at a constant height of 0.75m in the centre of the groundnut field to find out the concentration of uredospores, pathogenic to the crop, their correlation with the meteorological parameters and the growth stages of the crop. The aerobiological monitoring revealed that the maximum concentration of rust pathogen was observed in air during September in both the kharif seasons. Meteorological data was maintained in both the kharif seasons. The role of the meteorological factors for survival of the pathogen, growth stages of the crop and disease incidence has been discussed in the paper.